Basta Na Lang: Analyzing Absurdity Use in Selected RC Cola Commercials - Barba, Evian Jeline T. (Animo Repository, 2024)
Advertising permeates every aspect of everyday life, with companies often changing their strategies to engage and hook audiences with continually evolving tastes. Due to the dearth of research in the field of absurdity in advertisements, this qualitative study examines the usage of absurdity and humor within selected RC Cola commercials from the viral #BastaRCColaMasarap campaign. Using literary descriptors that define absurdity (Arias-Bolzmann et al., 2000) and humor categories (Catanescu & Tom, 2001), it explicitly addresses how the chosen commercials utilize absurdity, the reasoning behind said usage, as well as how it provides insights into Filipino humor culture. Findings revealed that the most utilized concept of absurdity is Surrealism, while their most common humor categories included exaggeration, silliness, surprise, and comparison. Absurdity and humor were found to be used as a coping mechanism for Filipinos, given the timing of the campaign’s release to the COVID-19 pandemic and how past literature points towards humor being used as a means to alleviate negative emotions (Nuncio, 2002; Balmores-Paulino, 2018). Finally, the research highlights how humorous absurdity is present in all of the analyzed commercials and further justifies how Filipino humor culture is both a coping mechanism and a tool for successful advertising using this marketing strategy.